A Coolie Woman, Trinidad - (:unkn) unknown (My University, 2008)
Includes a U.S.A one cent postage stamp dated May 10th 1906. Handwritten.
Colour: Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Postcards; Trinidad and Tobago; 1906; Women, East Indian--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Jewelry--India